TUYLU, ABDULLAH - HICRAN, NEZMIYYE (2018). LOVE POEMS IN TURKISH AND AZERBAIJAN LITERATURE "ANTHOLOGY" TOME: 1, SAKARYA: ORHUN PUBLICATIONS, ISBN 978-605-82128-2-4, 316 PAGES - Ali ÇELİK (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2019)
The named book Love Poems in Turkish and Azerbaijan Literature "Anthology" Tome: 1 were prepared by Abdullah Tüylü and Nezmiyye Hicran. It were given poems of some of the poets from Turkey and Azerbaijan in this book. General introduction of the book will be done and then some problems identified in the conclusion section will be mentioned